The influence of coordination of physical and psychological movements on music performance - Ning Dai, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to determine the effect of physical and psychological movement coordination on musical performance. This investigation also investigates the impact of mental tension on musical performance. This investigation has collected quantitative data on Likert scale 7-point questionnaire. This study's population consisted of trumpet players, and Smart PLS 3.0 was used to evaluate the measurement and structural models. This research has determined that the coordination of physical and psychological movements significantly affects musical performance. In addition, this study determined that when playing the trumpet, positive tension can make the performer concentrate and concentrate on performing, which is conducive to the play of the performance level and can also better interpret musical works. The research has demonstrated that in trumpet performance, the change of pitch, timbre, and intonation is primarily controlled by the coordination and cooperation of the physiological and psychological causes of stage tension in trumpet playing.